The Coronavirus Pandemic and Its Consequences on the Australian Economy in 2020 - Kandzia-Poździał, Agnieszka (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The fight against the Coronavirus continues around the world. The pandemic affects individuals and families and social groups, states, and economies. Like any other economy in the world, Australia’s economy has to deal with the effects of a pandemic. Australia has chosen its own way of fighting the disease and its consequences. It was not possible to avoid an economic recession, but at the same time, political decisions, aid provided, and social behaviour can be assessed as very effective.